2009
DOI: 10.1598/rt.63.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Engagement by Differentiating Independent Reading

Abstract: The authors provide teachers with a rationale for engaging students in independent reading using a differentiated approach. By profiling types of readers, sharing observational tools, and offering teaching suggestions for each type of reader the authors give practical suggestions to facilitate reading engagement and make independent reading more effective. يوفر المؤلفون للمعلمين عرضاً لأسباب تشغيل الطلاب في القراءة الانفرادية باستخدام طريقة متميزة. إذ يعطي المؤلفون اقتراحات عملية وظيفية لتسهيل إشغال القراءة وج… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Students engaged in self-selected independent reading and partner reading during the reading workshop time (the period after the initial mini-lesson when the teacher gathered together small groups and conferred). Both of these practices included researched-based instructional supports to scaffold independent reading (Bryan et al., 2003), teacher conferencing and student discussions (Kelley and Clausen-Grace, 2009), read-alouds to model fluent reading and strategy use (Pegg and Bartelheim, 2011) and establishing clear structures for participation in order to support emergent readers in the early stages of engagement (Mahiri and Maniates, 2013). The initial intervention was modified and expanded throughout the course of the year.…”
Section: Methodsmentioning
confidence: 99%
“…Students engaged in self-selected independent reading and partner reading during the reading workshop time (the period after the initial mini-lesson when the teacher gathered together small groups and conferred). Both of these practices included researched-based instructional supports to scaffold independent reading (Bryan et al., 2003), teacher conferencing and student discussions (Kelley and Clausen-Grace, 2009), read-alouds to model fluent reading and strategy use (Pegg and Bartelheim, 2011) and establishing clear structures for participation in order to support emergent readers in the early stages of engagement (Mahiri and Maniates, 2013). The initial intervention was modified and expanded throughout the course of the year.…”
Section: Methodsmentioning
confidence: 99%
“…If boys' literacy skills are to improve, they need to have literature that stimulates their interest and engages them in the process of reading. The need for engagement is reinforced by Kelley and Clausen-Grace (2009) whose study indicated that "highly engaged readers demonstrated higher levels of reading achievement than students who were less engaged" (p. 313). A motivating factor in students' interest in reading involves the ability of students to relate with the material.…”
Section: Literacy Skillsmentioning
confidence: 99%
“…Students with a qualified teacher-librarian in their schools are more likely to hold positive attitudes towards reading (Klinger, Lee, Stephenson, Deluca, & Luu, 2009;Lee & Klinger, 2011). Cultivating a positive attitude toward reading is vital, because a motivated reader reads and achieves more (Guthrie, Hoa, Wigfield, Tonks, & Perencevich, 2006) and is more likely to overcome barriers to literacy (Guthrie, Wigfield, & VonSecker, 2000;Kelley & Clausen-Grace, 2009). Highly motivated readers are enthusiastic, interested, involved, curious, and they persist, stay in school longer, learn more, and feel better about themselves (Furrer, Skinner, & Pitzer, 2014;Skinner & Belmont, 1993).…”
Section: Introductionmentioning
confidence: 99%